Pengembangan Kamus Arab-Indonesia sebagai Penunjang Penggunaan Buku Ajar Madrasah Tsanawiyah di Kelas VIII - Nurul Huda; Nabilah Ulfah (Prodi Pendidikan Bahasa Arab FTK UIN Sunan Ampel, 2019)
This study aims to produce a product in the form of an Arabic-Indonesian dictionary for 8th grade MTs to support the use of textbooks. Equipped with fi'il madhi, fi'il mudhari ’, and mashdar information for verbs in the form of verbs and for nouns equipped with singular and plural forms. The research model used is the Research and Development model. Methods of data collection in the form of non-tests using research instruments in the form of validation sheets, assessment sheets, and teacher and student response sheets on small scale trials and large scale trials. The results of this study are (1) have successfully developed Arabic-Indonesian dictionary products for grade 8 MTs, (2) based on the assessment of experts consisting of material experts, media experts and Arabic language teachers, this dictionary has very good quality (SB) , (3) based on a small-scale trial the students 'response to the product being developed was agreed (S) and on the large-scale trial the students' response to the Arabic-Indonesian dictionary for grade 8 MTs was strongly agreed (SS).